2006
DOI: 10.1111/j.1463-1326.2005.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel insulin analogues and its mitogenic potential

Abstract: Insulin analogues were developed to modify the structure of the human insulin molecule in order to more accurately approximate the endogenous secretion of insulin. With the help of recombinant technology and site-directed mutagenesis, the insulin molecule can be modified to either delay or shorten absorption time, providing better insulin treatment options and facilitating the achievement of glycaemic goals. Changing the structure of the insulin molecule, however, may significantly alter both its metabolic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 70 publications
0
30
0
1
Order By: Relevance
“…Curiously, this fact is not mentioned in the original report [44], which concludes with the statement that insulin glargine has a safety profile that, apart from reduced nocturnal hypoglycaemia, is 'otherwise similar to NPH insulin'. Equally curious, a later review also cites the same paper as documenting a three step or greater retinopathy progression in 7.5% of those on insulin glargine vs 2.7% of those on NPH (p<0.05) [45]. Since IGF-1 has a role in normal retinal vascular function and disease [46], this observation raised the possibility that insulin glargine might also have mitogenic effects on the vascular endothelium.…”
Section: Insulin Glargine and Retinopathymentioning
confidence: 99%
“…Curiously, this fact is not mentioned in the original report [44], which concludes with the statement that insulin glargine has a safety profile that, apart from reduced nocturnal hypoglycaemia, is 'otherwise similar to NPH insulin'. Equally curious, a later review also cites the same paper as documenting a three step or greater retinopathy progression in 7.5% of those on insulin glargine vs 2.7% of those on NPH (p<0.05) [45]. Since IGF-1 has a role in normal retinal vascular function and disease [46], this observation raised the possibility that insulin glargine might also have mitogenic effects on the vascular endothelium.…”
Section: Insulin Glargine and Retinopathymentioning
confidence: 99%
“…In order to create the insulin analogs, human insulin has been modified to more accurately mimic the endogenous secretion of insulin. Altering the structure of the insulin molecule can alter and enhance its mitogenic activity (Zib & Raskin 2006). The potential for increased cancer risk in patients treated with insulin analogs became a cause of alarm after a German study showed a dose-dependent increase in cancer risk in patients treated with one such analog, insulin glargine, compared with human insulin (Hemkens et al 2009).…”
Section: Exogenous Insulin and Cancermentioning
confidence: 99%
“…A significant concern regarding the use of the long-acting insulin analogs, has been the mitogenic potential of these analogues [Weinstein et al, 2007;Zib and Raskin, 2006]. Long-term clinical studies are needed to evaluate the use of insulin glargine or insulin detemir in pregnancy, both of which are currently classified Category C.…”
Section: Placenta Fetal Hyperglycemiamentioning
confidence: 99%